A Comparison Investigation on Antioxidant Activities, Constitutive Antifungal Phenolic Lipids and Phenolics Contents of Anthracnose Resistant and Susceptible Mango Fruit Cultivars. Issue 4 (1st October 2020) - Supriya, A.; Kumar, Amarjeet; Kudachikar, V. B.
ABSTRACT: The present study was conducted to find the constitutive antifungal phenolic lipids, phenolics contents and antioxidant activities in mango fruit peel extracts of anthracnose (Colletotrichum gloeosporioides Penz.) resistant ('Kensington pride') and susceptible ('Badami' and 'Raspuri') mango cultivars grown in India, during fruit development, maturity and ripening. Phytochemical tests were performed to determine 5-n-pentadecyl resorcinol content and total phenolics. Moreover, the mango peel methanolic extracts were subjected to evaluate their antioxidant potential using invitro DPPH assay. Results show that 5-n- pentadecyl resorcinol content in the mango fruit peel extract was at its peak during the early stage of fruit development (at 30DFS) in 'Kensington pride' as compared to 'Badami' and 'Raspuri'. The upsurge in total phenolics content and DPPH activity at 30 DFS, in all three mango cultivars, indicated their higher radical scavenging activity during fruit development than the fruit maturity and fruit ripening. Endogenous production and retention of high levels ( P ≤ .05) of constitutive antifungal 5-n-pentadecyl resorcinol in anthracnose resistant mango cultivar ('Kensington pride') during early stage of fruit development that imparts disease resistance during development, maturity, and fruit ripening process, could be one of the bases of plant defense mechanism against anthracnose disease. In conclusion, this study exhibited the important role played by the mango cultivars background on the constitutive antifungal 5-n-pentadecyl resorcinol content and antioxidant profiles.